Contemporary Challenges of Constitutionalism - Harutyunyan , G. (Bulletin of Yerevan University C: Jurisprudence, 2018)
Article discusses contemporary challenges of constitutionalism. Author justifies that constitutional identity of the individual is the complex of values and civil qualities, which determines the essential role and place of the individual as the direct holder of constitutional values and constitutional morality in constitutional-legal relations.
Keywords: constitutionalism, constitutional axiology, constitutional identity of the individual, Constitution